Pendayagunaan Irigasi Airtanah Menunjang Budidaya Tanaman Secara Produktif Pada Lahan Kering (The Utilization Of Groundwater Irrigation To Support Farming System In Dry Land Area) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
The Utilization of shallow groundwater well to support cropping pattern in thy land area should be directed to increase land and water pâ¢oductivities through proper irrigation management and effective operation of groundwater irrigation pump. By the concept that a certain plant needs a certain amount of transpired water through its leaves to produce 1 kg dry product during its production cycle, an attempt is done to determine technical and economic aspects of the groundwater irrigation system to utilize water and energy efficiently by improving the conjunctive use of rainfall and groundwater irrigation in thy land area. A set of centrifugal pump (0 2") was used to lift water from the shallow groundwater well at total head of 22 in (Suction head = 12 in and delivery head = 10 tn) and was used to irrigate maize, peanut and onion crops at different planting schedules depend on market demand. Furrow irrigation is used to apply supplemental water to crops. The result obtained indicates that the introduced technology is suitable to be applied at farm level. In order to reduce operational cost of pump, simulation was done to determine the most appropriate planting schedule using computer simulation model. By taking planting schedule back approximately-2 weeks reducing annual irrigation requirement of 500 to 600 in3/ha and reduce annual operation pump of 66,5 hour/ha/year.-140 hour/ha/year. Advanced analysis using economic feasibility analysis indicates technology introduced suitable to applied with B/C ratio = 1,25 (maize), 1,83 (peanut) and 2,36 (onion).